2010
DOI: 10.1021/ja9078144
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Simulation of NO Dioxygenation in Group I Truncated Hemoglobin

Abstract: NO dioxygenation, i.e., the oxidation of nitric oxide to nitrate by oxygen-bound truncated hemoglobin (trHbN) is studied using reactive molecular dynamics simulations. This reaction is an important step in a sequence of events in the overall NO detoxification reaction involving trHbN. The simulations ( approximately 160 ns in total) reveal that the reaction favors a pathway including (i) NO binding to oxy-trHbN, followed by (ii) rearrangement of peroxynitrite-trHbN to nitrato-trHbN, and finally (iii) nitrate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 84 publications
7
57
2
1
Order By: Relevance
“…This is usually not a limitation for reactions in the condensed phase. [36,38] However, for gas-phase reactions, final state analysis becomes meaningless. [32,35] Multi-Surface-ARMD (MS-ARMD) is an energy-based switching method which yields energy-conserving trajectories.…”
Section: Quantitative Intermolecular Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is usually not a limitation for reactions in the condensed phase. [36,38] However, for gas-phase reactions, final state analysis becomes meaningless. [32,35] Multi-Surface-ARMD (MS-ARMD) is an energy-based switching method which yields energy-conserving trajectories.…”
Section: Quantitative Intermolecular Interactionsmentioning
confidence: 99%
“…[25][26][27] Alternatively, if empirical and fully-dimensional force fields of sufficient accuracy can be parametrized, they offer a viable means to exhaustively sample phase space from which meaningful rate parameters can be determined. [28][29][30][31][32][33] One of the methods developed by us is adiabatic reactive MD (ARMD). Two variants exist for this: a time-based [29,34] and an energy-based switching scheme.…”
Section: Reactive Molecular Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even at 100 K, the purported peroxynitrite intermediate Fe III (TPP)(OONO -) was not observable, so it was concluded that once this species is formed, it must decay very rapidly to the more stable nitrate complex Fe III (TPP)(NO 3 -). Notably, different computational approaches also disagree on the potential stability of that intermediate [172,173]. Superficially, the reaction of O 2 with nitrosyl myoglobin Mb(NO) (27) appears similar to that of NO with Mb(O 2 ).…”
Section: Reactions With Dioxygenmentioning
confidence: 99%
“…Therefore, computer-assisted approaches have been developed to provide insight at an atomistic level. [31][32][33] Computational studies of dissociation processes have a long history. Due to the complexity of the problem, they initially focused on small molecules including H 2 O, ClCN, ICN, BrCN, and CH 3 I, and corresponding algorithms usually remained very specific for each molecule and question of interest.…”
Section: Introductionmentioning
confidence: 99%